2021
DOI: 10.1038/s41598-021-89673-8
|View full text |Cite
|
Sign up to set email alerts
|

Iron supplementation regulates the progression of high fat diet induced obesity and hepatic steatosis via mitochondrial signaling pathways

Abstract: Disruption of iron metabolism is closely related to metabolic diseases. Iron deficiency is frequently associated with obesity and hepatic steatosis. However, the effects of iron supplementation on obesity and energy metabolism remain unclear. Here we show that a high-fat diet supplemented with iron reduces body weight gain and hepatic lipid accumulation in mice. Iron supplementation was found to reduce mitochondrial morphological abnormalities and upregulate gene transcription involved in mitochondrial functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
(54 reference statements)
0
13
1
Order By: Relevance
“…Consistent with our results, Kitamura et al have recently demonstrated that 15 weeks of HFD intake supplemented with 0.023% ( w / w ) sodium ferrous citrate iron reduces body weight gain and hepatic lipid accumulation in male C57BL/6J mice. However, they also have shown that iron supplementation reduces mitochondrial abnormalities while increasing the transcription of genes associated with energy metabolism in the liver and skeletal muscle [ 32 ], which is contrary to our findings. On the other hand, Choi et al, who have used the same dose of carbonyl iron as ours in a shorter course (7 weeks), have found that HFD + Fe reduces SOD and glutathione peroxidase protein expression in mouse liver, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our results, Kitamura et al have recently demonstrated that 15 weeks of HFD intake supplemented with 0.023% ( w / w ) sodium ferrous citrate iron reduces body weight gain and hepatic lipid accumulation in male C57BL/6J mice. However, they also have shown that iron supplementation reduces mitochondrial abnormalities while increasing the transcription of genes associated with energy metabolism in the liver and skeletal muscle [ 32 ], which is contrary to our findings. On the other hand, Choi et al, who have used the same dose of carbonyl iron as ours in a shorter course (7 weeks), have found that HFD + Fe reduces SOD and glutathione peroxidase protein expression in mouse liver, which is consistent with our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…A recent report also implied that Bola3 was required for mitochondrial homeostasis and adrenaline-induced thermogenesis in both mouse beige adipocytes and human deep-neck brown fats [ 234 ]. In contrast, iron supplementation resulted in resistance to HFD-induced weight gain and hepatic lipid accumulation as the metabolic genes involved in the synthesis of heme and iron–sulfur clusters in the skeletal muscle and liver were upregulated [ 235 ]. Therefore, the manipulation of local and whole-body iron levels might be a therapeutic strategy for treating obesity and metabolic diseases in humans.…”
Section: Obesity and Mitochondrial Metabolismmentioning
confidence: 99%
“…Accordingly, deficiency in iron impairs mitochondrial function at many levels. ID has been linked to morphological changes in the mitochondria, such as an increase in size and a decrease in cristae [ 191 ], as well as functional changes such as reduced production of ATP [ 192 ], mitochondrial DNA damage [ 191 ], increased gluconeogenesis [ 187 , 193 ], increased lactic acid production [ 185 , 186 , 194 ], reduced mitochondrial biogenesis and impaired mitophagy [ 179 , 189 ], increased mitochondrial cytochrome c release (and hence apoptosis) and reactive nitrogen species expression [ 195 , 196 , 197 , 198 , 199 , 200 ]. All of this culminates in mitochondrial damage.…”
Section: Deleterious Biological Consequences Of Iron Deficiencymentioning
confidence: 99%